Transparenz im Schriftspracherwerb durch Family Literacy am Beispiel von “LIFE – Lesen in Familie erleben“ - Wiescholek, Sabrina; Hilkenmeier, Johanna; Buhl, Heike M. (Schulpädagogik heute)

Rezension zu: Nicola Kaminski; Volker Mergenthaler: Zuschauer im Eckfenster 1821/22 oder Selbstreflexion der Journalliteratur im Journal(text). Mit einem Faksimile des Zuschauers vom April/Mai 1822 - Öhlschläger, Claudia (Das achtzehnte Jahrhundert 40.2, 2016)

Gibbs measures on permutations over one-dimensional discrete point sets - Richthammer, Thomas; Biskup, Marek (Communications in Mathematical Physics)
We consider Gibbs distributions on permutations of a locally finite infinite set X⊂R, where a permutation σ of X is assigned (formal) energy ∑x∈XV(σ(x)−x). This is motivated by Feynman’s path representation of the quantum Bose gas; the choice X:=Z and V(x):=αx2 is of principal interest. Under suitable regularity conditions on the set X and the potential V, we establish existence and a full classification of the infinite-volume Gibbs measures for this problem, including a result on the number of infinite cycles of typical permutations. Unlike earlier results, our conclusions are not limited to small densities and/or high temperatures.

The rate of convergence to stationarity for M/G/1 models with admission controls via coupling - Kolb, Martin; Stadje, Wolfgang; Wübker, Achim (Stochastic Models)
We study the workload processes of two M/G/1 queueing systems with restricted capacity: in Model 1 any service requirement that would exceed a certain capacity threshold is truncated; in Model 2 new arrivals do not enter the system if they have to wait more than a fixed threshold time in line. For Model 1 we obtain several results concerning the rate of convergence to equilibrium. In particular, we derive uniform bounds for geometric ergodicity with respect to certain subclasses. For Model 2 geometric ergodicity follows from the finiteness of the moment-generating function of the service time distribution. We derive bounds for the convergence rates in special cases. The proofs use the coupling method.

Local asymptotics for the area of random walk excursions - Kolb, Martin; Denisov, Denis; Wachtel, Vitali (Journal of the London Mathematical Society)
We prove a local limit theorem for the area of the positive excursion of random walks with zero mean and finite variance. Our main result complements previous work of Caravenna and Chaumont; Sohier, as well as Kim and Pittel.

Serum sclerostin and DKK1 in relation to exercise against bone loss in experimental bed rest - Belavý, Daniel L.; Baecker, Natalie; Armbrecht, Gabriele; Beller, Gisela; Bühlmeier, Judith; Frings-Meuthen, Petra; Rittweger, Jörn; Roth, Heinz J.; Heer, Martina; Felsenberg, Dieter (Journal of Bone and Mineral Metabolism)
Keywords: Endocrinology; Orthopedics and Sports Medicine; General Medicine; Endocrinology; Diabetes and Metabolism

Glucocorticoid activity and metabolism with NaCl-induced low-grade metabolic acidosis and oral alkalization: results of two randomized controlled trials - Bühlmeier, Judith; Remer, Thomas; Frings-Meuthen, Petra; Maser-Gluth, Christiane; Heer, Martina (Endocrine)
Keywords: Endocrinology; Endocrinology; Diabetes and Metabolism

Towards a gendered history of European literary culture: a (not so) wild wish - Schlieper, Hendrik (PhiN 74)

La Querelle du Cid: la naissance de la politique culturelle française au XVIIieme siècle - Steigerwald, Jörn; Schlieper, Hendrik (Œuvres & Critiques XL,1. Coordinateurs du fascicule)

Neues Licht. Daguerre, Talbot und die Veröffentlichung der Fotografie im Jahr 1839. Steffen Siegel (Hg.): - Süwolto, Leonie (Zeitschrift für Germanistik. Neue Folge XXV)